2022
DOI: 10.3389/fneur.2021.770423
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered Evaluation of Meaningful Change on the 32-Item Motor Function Measure in Spinal Muscular Atrophy Using Qualitative and Quantitative Data

Abstract: The 32-item Motor Function Measure (MFM32) is an assessment of motor function used to evaluate fine and gross motor ability in patients with neuromuscular disorders, including spinal muscular atrophy (SMA). Reliability and validity of the MFM32 have been documented in individuals with SMA. Through semi-structured qualitative interviews (N = 40) and an online survey in eight countries (N = 217) with individuals with Types 2 and 3 SMA aged 2–59 years old and caregivers, the meaning of changes on a patient-friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Published natural history studies in untreated patients with types 2 and 3 SMA (ambulant and non-ambulant) have reported decline in RULM total score over 12 months (– 0.4 points in patients aged 2.7–49.7 years) [ 25 ] and 24 months (– 0.79 points in patients aged 5–56 years) [ 26 ] and HFMSE total score over 12 months (– 0.54 points in children and adults aged ≥ 2 years with a diagnosis before 19 years of age) [ 24 ], and significant decline over 24 months in MFM32 total score (– 2.08 points in patients aged 2–30 years) [ 21 ]. Although a 2-point (RULM [ 27 ]) or 3-point (HFMSE [ 27 ], MFM32 [ 28 ]) change in these functional motor scales has been highlighted as a clinically meaningful change, stabilization in motor function is an important goal identified by patients with types 2 and 3 SMA [ 29 , 30 ] and is, thus, considered a clinically meaningful outcome in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Published natural history studies in untreated patients with types 2 and 3 SMA (ambulant and non-ambulant) have reported decline in RULM total score over 12 months (– 0.4 points in patients aged 2.7–49.7 years) [ 25 ] and 24 months (– 0.79 points in patients aged 5–56 years) [ 26 ] and HFMSE total score over 12 months (– 0.54 points in children and adults aged ≥ 2 years with a diagnosis before 19 years of age) [ 24 ], and significant decline over 24 months in MFM32 total score (– 2.08 points in patients aged 2–30 years) [ 21 ]. Although a 2-point (RULM [ 27 ]) or 3-point (HFMSE [ 27 ], MFM32 [ 28 ]) change in these functional motor scales has been highlighted as a clinically meaningful change, stabilization in motor function is an important goal identified by patients with types 2 and 3 SMA [ 29 , 30 ] and is, thus, considered a clinically meaningful outcome in this population.…”
Section: Discussionmentioning
confidence: 99%
“…These improvements were often related to action directly associated with ADL that patients perform. Especially, as there were previous reports to correlate items of MFM with related ADL, [11,19] for patients above adolescent age with multiple contractures, the focus after Nusinersen treatment should be on improvement in ne motor function, which contribute to improvements in related ADLs. These aspects require properly evaluation using upper extremity assessment tools other than HINE-2 or HFMSE.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recommendations for the diagnosis and management of SMA, [5,6] the Hammersmith Infant Neuromuscular Examination Section 2 (HINE-2), [7] and the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP-INTEND) [8] are appropriate for non-sitters, and the Hammersmith Functional Motor Scale Expanded (HFMSE), [9] Revised Upper Limb Module (RULM), [10] Motor Function Measure (MFM), [11] and 6 minute walk test (6-MWT) [12] are recommended for sitters and above. In addition, the Adult Test of Neuromuscular Disorders (CHOP-ATEND), a modi ed version of CHOP-INTEND, is a recently developed and recommended tool for chronic adult patients with severe joint contracture and di culty with wheelchair transfers.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of this study lies in its qualitative collection of perspectives from patients with advanced or metastatic NSCLC, using their prior experience with disease (6-12 months prior) compared with their current state (last 7 days). This contrasts with discretechoice experiments (Duong et al, 2021;Raymond et al, 2021), which, while powerful, focus on hypotheticals and may fail to observe underlying relationships between baseline characteristics, symptom severity, and impacts on activities of daily living that drive decisionmaking. Our study used established PGI-S and PGI-C items within qualitative interviews to better define the patient's perspective of meaningful change in NSCLC and strengthen quantitative evaluations from PRO instruments.…”
Section: Impact (Mentions) Quotementioning
confidence: 97%